Mandapa (pillared hall) of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The mandapa (pillared hall) of the Hazareshwar Temple is a small square open hall that stands on a low base, supported by four pillars positioned at its corners. These pillars feature square bases adorned with depictions of deities. The shaft of the pillars is intricately carved with male deities, musicians, dancers, and surasundaris (celestial damsels). Transitioning into an octagonal shape, then into sixteen facets and circular, the shaft culminates with an abacus supporting bharavahaka (load bearers) brackets, which in turn uphold the lintel. The mandapa's ceiling, square in shape, is exquisitely carved. There is an idol of Nandi housed at the centre of the mandapa.